MENINGKATKAN REGULASI DIRI ANAK-ANAK PANTI ASUHAN DAN SANTUNAN KELUARGA MUHAMMADIYAH ‘AISYIYAH CABANG PULOGADUNG-RAWAMANGUN - Naomi Soetikno; Clarita Andreane; Novita Levina Kosman; Eliana Clarissa Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Adolescence is a developmental transition process towards early adulthood. The transition of individual roles and responsibilities is a challenge in itself, because individuals are not yet fully mature, but are no longer children. According to the results of interviews with caregivers, the problems that arise in adolescents in the orphanage are the lack of initiative and self-regulation. The skills needed for self-regulation are the ability to monitor oneself, regulate behavior, make decisions for oneself and others, manage feelings of frustration and difficulty effectively, and also the ability to manage stress. Therefore, this program is designed based on five dimensions in developing self-regulation. The meetings were held 6 times through Zoom Cloud meetings and the distribution of pre-test and post-test questionnaires to caregivers was made in a google form, using the Short Self-Regulation Questionnaire as a measuring tool. Based on the results of the activity pre-test, the highest points obtained were in the goal setting dimension with a value of 8.5 points, and the lowest was in the mindfulness dimension with 5.7 points. After the implementation of the program, the overall post-test results showed that the children had improved in every dimension, except for the proactiveness dimension. Therefore, self-regulation training programs can be developed more properly to improve every aspect of self-regulation in order for adolescents to actualize the future they want to achieve.